EDUCATION OF THE IMPACT OF ORAL BAD HABITS IN CHILDREN ON THE OCCURRING OF DENTAL MALOCLUSION IN THE COMMUNITY OF THE WORKING AREA OF THE MARGASARI PUSKESMAS, TEGAL - Novianty, Shella Indri; Putri, Adisty Restu; Mayangsari, Regilia Shinta; Nurazky, Savira; Indrawati, Silvia Vera; Pratama, Muhammad Dimas Putra (Faculty of Dentistry Universitas Islam Sultan Agung, 2023)
Background: Malocclusion is a condition of deviation of the arrangement of the teeth from the dental arch outside the acceptable range. This condition is influenced by various factors. One of the external factors that is widely suspected as the cause of malocclusion is bad habits that are carried out in childhood so that it affects the growth of the jaw and results in changes in the arrangement of teeth. In Indonesia, the prevalence of malocclusion is estimated at 80% and is the third largest dental and oral problem after caries and periodontal disease. Method: The method used in this study uses the method of counseling material on the importance of knowing bad habits in children and how to prevent them. This research includes experimental research conducted directly in the working area of the Margasari Health Center. The data obtained will be processed in SPSS and tested. Result: This study resulted in data that after counseling and delivery of material by the team, the community had a higher level of awareness. This result is supported by a significant difference between before and after counseling. This is important because bad habits in children will have an impact on adulthood. Conclusion: The community in the working area of the Margasari Health Center showed good and significant results after being given the material on the importance of knowing bad habits and their prevention.